PENINGKATAN KEMAMPUAN ASESMEN MAHASISWA CALON GURU KIMIA MELALUI PENGEMBANGAN PROGRAM PERKULIAHAN EVALUASI PEMBELAJARAN KIMIA BERBASIS INKUIRI - Nahadi, Mr; Liliasari, Mrs (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2010)
This research had been conducted to find study program which can increase ability of chemistry prospective teachers for doing assessment chemistry learning. Research process is held in LPTK in Bandung by 52 teacher candidates at validation test and 112 teacher candidates at implementation test. Design research and development is applied with four phases. Those were 1) preliminary study; 2) program planning; 3) program validation; and 4) program implementation. Data collected through test of the chemistry education evaluation theory, prospective teachers activity, and exercises. Data was collected using test, observation sheet, portfolio, questionnaire and field note. Data analysis used descriptive statistics of normalized gain score by t test. The research produced an inquiry based chemistry education evaluation program (PEPKBI). The program was consist of design, implementation and evaluation of learning Chemistry components. Results of research indicated that PEPKBI program was effective to increase score of the evaluation of chemistry learning theory (<g> = 0,462),Keywords: assessment, chemistry learning, program development